Deprivation of parental rights: a safety net for children or parents? - Tasic, Andjelija (European Integration Studies, 2023)
The family, the primary and most suitable place for growth and well-being, can be jeopardized by the misbehavior of its members. In accordance with its duties, the State should take appropriate measures to protect family members, especially the children. This paper focuses on the deprivation of parental rights and its normative and theoretical framework as a court measure for children’s protection. Presenting the results of research that considers cases in front of the Basic Court of Niš, this study aims to determine the reasons for the deprivation of parental rights, difficulties that occurred in the proceedings, and ways to overcome them.